Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the restricted values for the expression \(\frac{x^2-4}{4 x^2-12 x} \cdot \frac{2 x+4}{-x^2+5 x-6}\), we must determine the values of \(x\) that make any denominator equal to zero, as division by zero is undefined.
Let's consider the denominators in the given expression:
1. The first denominator is \(4x^2 - 12x\).
2. The second denominator is \(-x^2 + 5x - 6\).
We will find the values of \(x\) that make each denominator equal to zero.
### Step 1: Solve \(4x^2 - 12x = 0\)
First, factor this quadratic expression:
[tex]\[4x^2 - 12x = 4x(x - 3) = 0\][/tex]
Set each factor equal to zero:
[tex]\[4x = 0 \quad \Rightarrow \quad x = 0\][/tex]
[tex]\[x - 3 = 0 \quad \Rightarrow \quad x = 3\][/tex]
So, the values of \(x\) that make this denominator zero are \(x = 0\) and \(x = 3\).
### Step 2: Solve \(-x^2 + 5x - 6 = 0\)
We can rewrite and factor this quadratic expression:
[tex]\[ -x^2 + 5x - 6 = 0 \][/tex]
Multiply the equation by \(-1\) for easier factoring:
[tex]\[ x^2 - 5x + 6 = 0 \][/tex]
Factor the quadratic expression:
[tex]\[ x^2 - 5x + 6 = (x - 2)(x - 3) = 0 \][/tex]
Set each factor equal to zero:
[tex]\[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \][/tex]
[tex]\[ x - 3 = 0 \quad \Rightarrow \quad x = 3 \][/tex]
So, the values of \(x\) that make this denominator zero are \(x = 2\) and \(x = 3\).
### Combine Restricted Values
From both steps, the restricted values of \(x\) are \(x = 0\), \(x = 2\), and \(x = 3\).
### Final Answer
Combine the restricted values:
[tex]\[ \boxed{0, 2, 3} \][/tex]
Therefore, the correct answer is:
[tex]\[x \neq 0, x \neq 2, x \neq 3\][/tex]
Thus, the correct choice is:
B. [tex]\(x \neq 0, \neq 2, \neq 3\)[/tex]
Let's consider the denominators in the given expression:
1. The first denominator is \(4x^2 - 12x\).
2. The second denominator is \(-x^2 + 5x - 6\).
We will find the values of \(x\) that make each denominator equal to zero.
### Step 1: Solve \(4x^2 - 12x = 0\)
First, factor this quadratic expression:
[tex]\[4x^2 - 12x = 4x(x - 3) = 0\][/tex]
Set each factor equal to zero:
[tex]\[4x = 0 \quad \Rightarrow \quad x = 0\][/tex]
[tex]\[x - 3 = 0 \quad \Rightarrow \quad x = 3\][/tex]
So, the values of \(x\) that make this denominator zero are \(x = 0\) and \(x = 3\).
### Step 2: Solve \(-x^2 + 5x - 6 = 0\)
We can rewrite and factor this quadratic expression:
[tex]\[ -x^2 + 5x - 6 = 0 \][/tex]
Multiply the equation by \(-1\) for easier factoring:
[tex]\[ x^2 - 5x + 6 = 0 \][/tex]
Factor the quadratic expression:
[tex]\[ x^2 - 5x + 6 = (x - 2)(x - 3) = 0 \][/tex]
Set each factor equal to zero:
[tex]\[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \][/tex]
[tex]\[ x - 3 = 0 \quad \Rightarrow \quad x = 3 \][/tex]
So, the values of \(x\) that make this denominator zero are \(x = 2\) and \(x = 3\).
### Combine Restricted Values
From both steps, the restricted values of \(x\) are \(x = 0\), \(x = 2\), and \(x = 3\).
### Final Answer
Combine the restricted values:
[tex]\[ \boxed{0, 2, 3} \][/tex]
Therefore, the correct answer is:
[tex]\[x \neq 0, x \neq 2, x \neq 3\][/tex]
Thus, the correct choice is:
B. [tex]\(x \neq 0, \neq 2, \neq 3\)[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.